2020
DOI: 10.1111/ap.12423
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and selective attention predict dysmorphic concern in an Australian university population

Abstract: Objective There is a paucity of research investigating the underlying aetiological mechanisms contributing to dysmorphic concern. In the present study, we used a multidimensional measure of perfectionism and a dot‐probe task, borrowed from the dysmorphic concern and body dysmorphic disorder literature, to assess associations between subtypes of perfectionism (i.e., concerns and strivings), selective attention towards target word stimuli (i.e., DC‐body, DC‐negative, and DC‐positive words), and dysmorphic concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Therefore, these two dimensions of adaptive perfectionism can encourage someone to become obsessed with achieving a perfect appearance. S. Johnson et al (2020) showed that perfectionism and selective attention can predict dysmorphia concerns in both adult men and women. Perfectionism and body image issues have also been found to be positively related to the appearance of BDD symptoms (Arji et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these two dimensions of adaptive perfectionism can encourage someone to become obsessed with achieving a perfect appearance. S. Johnson et al (2020) showed that perfectionism and selective attention can predict dysmorphia concerns in both adult men and women. Perfectionism and body image issues have also been found to be positively related to the appearance of BDD symptoms (Arji et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have found an association between social media pressure and body dissatisfaction and eating disorders (Perloff, 2014;Sukamto et al, 2019), no study has been made which links it to BDD. Furthermore, there is a lack of research that examines the relationship between perfectionism and BDD tendencies in Indonesia, even though research has been conducted in several other countries, such as Iran, the US, and Australia (Arji et al, 2016;Foroughi et al, 2019;S. Johnson et al, 2020;Phillips, 2009) shows that perfectionism can play an important role in a person's tendency to experience BDD.…”
Section: Introductionmentioning
confidence: 99%